PHOTOGRAPHY AND FASHION (Conferencea, 2024)
The publication examines fashion and photography as a single captivating blend of art, style and storytelling. Photography and the Unity of Fashion detail the diverse evolution of fashion that remains in history. The development of fashion photography and its socio-cultural significance are described.